EKOLOGI MOLUSKA MANGROVE DELTA MAHAKAM, KALIMANTAN TIMUR - Heryanto - - (Masyarakat Zoologi Indonesia, 2008)
Heryanto. 2008. Ecology of mangrove moluscs in Delta Mahakam, EastKalimantan. Zoo Indonesia 17(1):15-20. A survey on the ecology of mangrovemolusc in Delta Mahakam, East Kalimantan was conducted for two weeks. Collectionsof gastropods were conducted along the transect line developed for botany study.Result had collected 20 species of gastropods, which was represented the westernIndonesia pattern, hence it accommodates less variety of gastropods. The numberwas also influenced by the forest condition. When the forest was in good condition,species number of gastropods (â‰ˆbiodiversity) live in forest was high and vice versa.